2015
DOI: 10.1097/md.0000000000001708
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Coronary Severity, Outcome and ABO Blood Group

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Second, a multiplier was assigned to each main vascular segment based on the functional significance of the myocardial area supplied by that segment: 5 for the left main coronary artery, 2.5 for the proximal segment of the left anterior descending (LAD) coronary artery, and the proximal segment of the circumflex artery, 1.5 for the mid-segment of the LAD, 1.0 for the right coronary artery, the distal segment of the LAD, mid-distal region of the circumflex artery, the posterolateral artery, and the obtuse marginal artery, and 0.5 for small segments. 15,18 Follow-Up…”
Section: Severity Assessment Of Coronary Atherosclerosismentioning
confidence: 99%
“…Second, a multiplier was assigned to each main vascular segment based on the functional significance of the myocardial area supplied by that segment: 5 for the left main coronary artery, 2.5 for the proximal segment of the left anterior descending (LAD) coronary artery, and the proximal segment of the circumflex artery, 1.5 for the mid-segment of the LAD, 1.0 for the right coronary artery, the distal segment of the LAD, mid-distal region of the circumflex artery, the posterolateral artery, and the obtuse marginal artery, and 0.5 for small segments. 15,18 Follow-Up…”
Section: Severity Assessment Of Coronary Atherosclerosismentioning
confidence: 99%
“…Clinical trials determined that blood group types are associated with CAD. 5,[26][27] A recent meta-analysis confirmed that non-O blood groups appear to be an independent risk factor for CAD and myocardial infarction. 28 Non-O blood groups have been found to show a significant relationship with family history of CAD and hypercholesterolemia, and this might be a possible genetic interaction between blood groups and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is acknowledged that blood type groups are associated with CAD. 4,5 Genome-wide association studies have determined a significant association between the blood type group genes and inflammatory marker genes. [6][7][8][9] Blood group types frequency is different in different areas of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The ABO blood group is considered an overarching genetic determinant of CVD risk [7]. Advances in technology, biochemistry, and genetics have clarified to a plausible extent the association of blood group typesespecially the human blood group antigens, A, B, and H (O)and their relationship to risk for disease [8].…”
mentioning
confidence: 99%
“…Extensive, evidence-based, scientific validation has substantiated the association between ABO blood groups and diseases such as cancer, infection, coagulation disorders, diabetes, and CVD [8,9]. Thus, the study of ABO blood group phenotypes remains a fascinating field, given its role in the pathogenesis of different diseases, particularly CVD [7,9]. The influence of ABO blood groups on the cardio-metabolic health status of an individual is multifaceted, because MUH status and the risk of CVD is a multi-factorial condition that is not controlled by just a single blood group antigen [8].…”
mentioning
confidence: 99%